2018
DOI: 10.4103/sjg.sjg_438_17
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation in adolescents with irritable bowel syndrome: Is it useful? A randomized controlled trial

Abstract: Background/Aim:Vitamin D deficiency is common in irritable bowel syndrome (IBS). There is growing interest in the role of vitamin D in pediatric IBS. We aimed to evaluate the effect of vitamin D supplementation in adolescents with IBS and vitamin D deficiency.Patients and Methods:One hundred and twelve adolescents with IBS and vitamin D deficiency were randomly divided into two groups of matched age and sex. The first group received oral vitamin D3 2000IU/day for 6 months and the second group received placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 30 publications
5
50
2
2
Order By: Relevance
“…Intake of 1 pearl of vitamin D3 containing 50,000 IU per week for 9 weeks increased serum 25(OH) vitamin D3. The same results have been reported by previous work assessing the effect of vitamin D on IBS patients [23][24][25].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Intake of 1 pearl of vitamin D3 containing 50,000 IU per week for 9 weeks increased serum 25(OH) vitamin D3. The same results have been reported by previous work assessing the effect of vitamin D on IBS patients [23][24][25].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, studies demonstrated that vitamin D deficiency is related to symptoms of psychological disorders [21,22]. It goes without saying that the mechanism of the effect of vitamin D on IBS symptoms is not quite clear in recent trials [23][24][25]. In this study, we hypothesized that DOI: 10.1159/000506149 vitamin D may improve clinical symptoms by ameliorating mental state [21,26] and by anti-inflammatory effects [27,28].…”
Section: Introductionmentioning
confidence: 90%
“…This was in accordance with the results reported in another Egyptian study conducted on 112 adolescents which reported a significant improvement in the clinical status of patients with IBS who received vitamin D compared to the placebo group. 8 In an Iranian study, there was a statistically significant improvement (p < 0.05) in most IBS symptoms among patients receiving 50.000 IU vitamin D 3 every two weeks for 6 months 1 . Contrary to these results, IBS symptoms were not significantly improved in an English pilot trial conducted on 51 patients with IBS after 12 weeks of daily 3000 IU vitamin D 3 supplementation.…”
Section: Resultsmentioning
confidence: 94%
“…Results showed that the baseline difference between the intervention and the control groups regarding IBSSSS was statistically insignificant (p=0.078). However, after the intervention, patients receiving vitamin D 3 7,8 the mechanism behind this is still a controversy. 12 The present study was conducted to assess the effect of oral vitamin D 3 supplementation (Cholecalciferol) on gastrointestinal symptoms in patients with IBS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation